Implementation Of Regional Financial Management Information System (SIPKD) In Enhancing Local Financial Accountability In Tapanuli Selatan District - Henny Wahyuni Nasution; Syafaruddin Ritonga; Nina Siti Salmaniah (MultiTech Publisher, 2024)
This research is titled